Effect of topical application of juvenile hormone (JH) in honeybee worker larvae on the development of the Dufour's and Koschewnikow's glands - Abdalla, Fábio Camargo [UNESP]; Gracioli, L. F.; Salles, H. C.; Cruz-Landim, Carminda da [UNESP]; Moraes, R. L M. Silva de (California State University, 2001)
In order to investigate the action of the juvenile hormone (JH) on honeybee caste differentiation two exocrine glands, Koschewnikow and Dufour glands, were chosen for study. Two combs (I & II) were taken from a single posture of a queen to use for this research. In comb I the larvae were treated with a topical application of JH in Acetone, and those from the comb II (control group) received only Acetone. Immediately after the emergence of the workers, their glands were dissected and prepared for microscopic measurements. The results showed cell area reduction in the Koschewnikow gland induced by the JH application. The results for the Dufour gland displayed taller epithelial cells with the JH application. The difference in glandular responses to the JH relates to gland function, hormone targets, and individual homeostasis.
Keywords: Apis mellifera; Koschewnikow glands; Dufour glands; juvenile hormone; morphometric analysis